SYNESTHESIA AND THE AUTISM SPECTRUM DISORDER (ASD) - Tomasi, Maria Cecilia; Brandes, Jaciara Muller; Lopes, Juliana; Klostermann, Henrique Sartori; Cyrino, Luiz Arthur Rangel (Journal of Health Care, 2018)
Introduction: Synesthesia, which has a prevalence of 4%, is a neurological condition in which a single stimulus elicits additional experiences from another sensory sense, which can be: visual, auditory, olfactory, gustatory and tactile. This condition is not included in the DSM-5, however, its neurological bases may be linked to some behavioral disorders present in other disorders, such as Autism Spectrum Disorder (ASD). Objective: To perform a literature review on synesthesia and its possible correlation with ASD. Materials and methods: A bibliographic survey was carried out through the electronic databases: PubMed, Science Direct, SciELO, Google Academic and Research Gate, including articles and books, published in Portuguese and English. Between 1995 and 2015, to document synaesthesia and ASD. Results: To compose the present review, 37 articles and 4 books, national and international were included. Studies have shown that the prevalence of synesthesia is higher in autistic individuals. Other results point to similarities in the neurological and genetic bases involved in ASD and synesthesia, which explain altered sensorial perceptual processing in both. Conclusion: In this article, therefore, it was seen through different studies that synesthesia and TEA may present a correlation and that its aspects present a challenge for future research.
Keywords: Synesthesia; perception; autism; psychology; neurology